The role of stem cell niche in intestinal aging. (October 2020) - Pentinmikko, Nalle; Katajisto, Pekka
Highlights: Intestinal function declines with age. Regenerative capacity of intestinal stem cells is reduced due to alterations in the niche. Differentiation towards the Paneth cell lineage is increased in the old intestine. Targeting niche by lifestyle changes or pharmacological agents can improve function of the aged intestine. Abstract: Like most tissues, intestine shows multiple alterations during aging. While the main function of nutrient absorption is relatively well maintained, capacity of the intestine to respond to abrupt changes or damage declines with age. The reduction in renewal and regeneration capacity results from alterations in the stem cells that renew the epithelium, and in the complex interactions stem cells have with their microenvironment, or the Niche. This review highlights recent evidence on age-associated changes in the intestinal stem cell function, and focuses on stem cell extrinsic mechanisms. Strategies targeting niche interactions have already shown promise in alleviating problems associated with intestinal aging in animal models, and may provide means to protect the elderly for example from chemotherapy induced gastrointestinal side-effects.